Development and psychometric evaluation of a rapid intimate partner violence perpetration screening tool. Issue 2 (30th November 2017) - Crane, Cory A.; Rice, Samara L.; Schlauch, Robert C.
Abstract : Current methods of identifying intimate partner violence (IPV) perpetration rely upon lengthy screening instruments, partner injury, and legal involvement. There exist no viable, brief screening tools to facilitate the rapid and early identification of IPV perpetration. The development of a brief IPV screening tool would reduce participant burden and compensation in research as well as aid in self‐identification and appropriate consultation for treatment. Three samples were recruited and administered an IPV assessment measure. Receiver Operating Characteristic (ROC) curve analyses were used to determine a critical subset of items that could be rapidly administered and used to accurately detect physical IPV perpetrators. A set of four items emerged that were capable of differentiating between partner violent and nonviolent participants in Samples 1 (the Area Under the ROC Curve (AUC) = .95, SE = .02), 2 (AUC = .98, SE =.01), and 3 (AUC = .94, SE = .04). Internal consistency of the screening items was acceptable across samples and the scores on the screening tool were significantly associated in the expected direction with all assessed risk factors for IPV. Initial evaluation of the rapid IPV perpetration screening tool suggests that it may help satisfy the growing need to quickly determine research eligibility and to help college students self‐identify risk, offering objective data upon which to base the decision for follow‐up consultation.